The threat of «regional trends» in organization of the youth movement in Siberia in the 1920’s - R. V. Rybakov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study of the regional characteristics the development of the communist youth movement in the 1920's on the example of Omsk. The problem of local organizations separatism and the charges against them in an attempt to revive Siberian regionalism are analyzed. The revealed documents allow us to conclude that, despite the consonance of some of the demands of young people to the ideas of regional leaders, there was no regional movement among them. The accusation was a necessary measure, designed to explain the difficulties in implementing the tasks assigned to the Sibbureau in the region